Marketing Communication Analysis in Building Client Trust in An Airline Service Company - Dermawan, Muhammad Akmal; Saputra, Faisal Tomi; Irianti, Een (Peneliti.net, 2023)
This study aims to determine the Marketing Communication Strategy implemented by PT. Garuda Daya Pratama Sejahtera (GDPS) in building Client trust and analyzing the extent to which IMC (Integrated Marketing Communication) Theory is applied by PT. Garuda Daya Pratama Sejahtera in building client trust The type of research conducted is descriptive qualitative with a case study method or approach. The results of the study show that GDPS has transformed into a technology-based Business Processing Outsourcing (BPO) 4.0 company that not only serves aviation needs, but also penetrates into other businesses. The marketing strategy used until 2022 is the marketing mix strategy or marketing mix 4P, namely Product, Price, Place and Promotion. To build client trust, now GDPS has combined conventional marketing communication strategies with modern marketing strategies and continues to innovate by integrating information system technology into its marketing strategy to become integrated marketing or integrated marketing communication (IMC).